Michelman forms partnerships with Mafic & EFT for innovation & product development. Issue 2 (February 2018) - Unknown
Abstract : Sizing and surface treatments specialist Michelman has recently entered into two separate partnerships, the first with basalt fibre producer Mafic SA and the second with speciality fibres manufacturer Engineered Fibers Technology LLC (EFT). Both alliances target the development of innovative products for high-performance composites.